Manufacturing Shintō as a “World Religion” - MacWilliams, Mark (Journal of Religion in Japan, 2018)
How is Shintō presented in Anglo-American world religions textbooks? While not included in the earliest of such survey courses, it regularly appears in such texts from the early 20th century to the present. Why is Shintō included as one of “great” or “world” religions given how greatly it differs from the likes of Christianity and Islam? Textbook authors include Shintō by constructing an image of it that reflects their own model of world religions, an image that is also based on the “Shintō” that Meiji Japanese officials and scholars invented for their own political-ideological purposes. The standard portrayal of Shintō in Western textbooks has remained more or less the same for a century: It is described as (1) an archaic religion; (2) centered on Japanese imperial mythology; (3) nature worship; (4) apolitical, emphasizing personal piety at shrines. While the most recent editions have tried to incorporate new scholarship in their portrayal, they still rely a world religions model of Shintō that is seriously misleading, failing to adequately present Shintō’s complexities as a tradition.